Experimental investigation of tunnel fire spread under moving fire source conditions - Tong Wang; Yi Qin; Zhihao Zhang; Yue Xiang; Xiong Zhu; Tao Fan (PLoS ONE, 2026)
Fires caused by moving fire sources are more complex and hazardous than those initiated by stationary sources. In tunnel fire scenarios, ignition sources often vary in velocity and elevation, which markedly affect fire dynamics. A small-scale experimental platform was employed to examine the impact of fire source height and speed on flame behavior, smoke propagation, and temperature distribution in tunnel fires. The experimental results demonstrate that the critical velocity associated with noticeable flame attenuation exhibits a distinct non-monotonic dependence on fire-source elevation. Specifically, as the height increases from 7.5 cm to 10 cm, the critical velocity rises from 0.3 m/s to 0.8 m/s, yet decreases to 0.5 m/s at 12.5 cm. At a fixed height, increasing the movement speed from 0.1 m/s to 1.0 m/s reduces flame height by up to 40% and increases the flame tilt angle by more than 50%. Conversely, at a constant speed, flame tilt angle first decreases and then increases with increasing fire source height, while flame height initially rises and then falls. A clear quantitative relationship is identified between flame height and movement speed; specifically, the ratio of flame height (L) to effective tunnel height (H) shows a distinct functional relationship with ( Q 1 / 3 H 1 / 3 ! / v . Moreover, Smoke layer thickness decreases with increasing fire source height. The reverse smoke flow length increases and then decreases with increasing fire source speed. Ceiling temperatures show a pronounced dependence on movement speed: at 0.1 m/s, the peak temperature reaches 89.4°C with a height-induced variation of approximately 20°C, whereas at 1.0 m/s, the peak drops to 37°C and the temperature difference narrows to about 2°C.